2015
DOI: 10.1007/s00247-015-3439-0
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric elbow fractures: a new angle on an old topic

Abstract: Supracondylar fractures are the most frequent elbow fracture seen initially, followed by radial neck, lateral condylar, and olecranon fractures in a distribution different from what has been historically described. The relatively high frequency of olecranon fractures detected on follow-up speaks to their potentially occult nature. Careful attention to these areas is warranted in children with initially normal radiographs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 13 publications
1
38
0
2
Order By: Relevance
“…From the distribution according to sex in previous study from Esen and Sapmaz and Anjum et al, male patients sustained more elbow fractures compared than female patients [5], [6]. This is in line with the result of our study in which the male patients dominantly suffered elbow fractures than the female patients while a retrospective study about pediatric elbow fractures conducted by Emery et al showed no differences in the demographic pattern of sex [7].…”
Section: Discussionsupporting
confidence: 91%
“…From the distribution according to sex in previous study from Esen and Sapmaz and Anjum et al, male patients sustained more elbow fractures compared than female patients [5], [6]. This is in line with the result of our study in which the male patients dominantly suffered elbow fractures than the female patients while a retrospective study about pediatric elbow fractures conducted by Emery et al showed no differences in the demographic pattern of sex [7].…”
Section: Discussionsupporting
confidence: 91%
“…1,2 Diagnostic radiology is an essential component of proper evaluation, however, interpretation of pediatric elbow radiographs is complicated by the cartilaginous components of the elbow that are radiolucent. 3 Assessment of these radiographs depends on evaluating the anatomic relationships of the ossification centers of the elbow, including the position of the radial head relative to the capitellum, anterior humeral line relative to the capitellum, and Baumann’s angle.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The most common fractures are supracondylar humerus fractures, radial neck fractures, lateral condyle fractures, and medial epicondyle fractures. 1 Interpretation of pediatric elbow radiographs is complicated by the cartilaginous nature of the immature elbow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fractures of the lateral condyle are the second most frequent elbow fracture in children after supracondylar fracture, comprising 10-20% of all paediatric elbow fractures. 1,2 Despite this, the injury remains relatively rare, with a reported incidence of 1.6/10,000. 3,4 The mechanism of injury is either through an avulsion of the condyle due to a varus force on a supinated forearm or through radial head impaction on the capitellum following a fall onto an outstretched hand.…”
Section: Introductionmentioning
confidence: 99%